Nursing care of a patient with cholelithiasis based on integrated medical and nursing ward rounds model (医护一体化模式下1例胆石症患者的护理体会) - QI Huan (祁欢); XU Bing (许冰); LIU Miao (刘苗) (中西医结合护理)
This paper reviewed the clinical data of a patient with cholelithiasis, and summarized the treatment and nursing experience under the integration of medical and nursing model. Based on the medical and nursing integration model, appropriate nursing techniques of Traditional Chinese Medicine including auricular acupoint sticking and pressing therapy, manipulation massage treatment and acupoint sticking treatment were carried out. Targeted psychological care and health education were conducted after analysis on patient’s emotional status. Nursing intervention based on the medical and nursing integration model can effectively reduce the clinical symptoms of the patient, relieve negative emotion and improve the recovery of the patient with cholelithiasis. (本文总结医护一体化模式下1例胆石症患者的护理体会。基于医护一体化模式, 通过辨证施护, 给予耳穴贴压、推拿、穴位贴敷中医护理适宜技术, 并针对患者情绪状态, 开展心理干预、健康宣教等护理措施, 改善患者疼痛症状, 缓解负性情绪, 促进早期康复。)